Mapping over 80 years of wetland sensitivity to human intervention. The spatial dynamics of the lakes and wetlands of the Jijia-Iași Wetlands Ramsar Site in 1935–2018 - Albulescu, Andra-Cosmina; Minea, Ionuț; Larion, Daniela; Iosub, Marina; Boicu, Daniel (Journal of environmental engineering and landscape management, 2023)
Wetlands are at the top of the list in terms of valuable ecosystem services, at the same time being one of the most sensitive ecosystems that are subject to human-induced changes. The delicate balance between their ever-changing waterlogged and dry areas, together with the associated rich flora and fauna, are easily disturbed by human drivers, which are also responsible for long-term land use conversions. This paper aims to 1) document the spatial dynamics of the wetland areas and lakes in the Jijia-Iași Wetlands Ramsar Site, using historical cartographic materials and modern land use data, and 2) pinpoint the anthropic drivers that shaped these dynamics, via a literature review. This Ramsar Site constitutes an eloquent example of a wetland landscape that was mainly shaped by human intervention. A timeline is used to put into perspective the resulting maps and synthesised findings, and several inferences regarding the past, present, and future sensitivity of the wetlands in the study area are formulated. In 1935–2018, the two analysed elements followed opposite trends: while the wetland areas decreased from 10.61% of the study area to 4.79%, the lake features increased in size, from 0.68% of the Jijia-Iași Wetlands to 10.84%. In order to explain these changes, anthropogenic interventions were divided into three types of management (detrimental high human pressure, beneficial high human pressure, and beneficial low human pressure). In the long term scientific works, the unbalanced dynamics proved to be beneficial to the environment, as the construction of water collections determined a biodiversity boost and the designation of the study area as a Ramsar Site. This paper complements the scientific work focusing on “the Delta of Moldavia”, highlighting the practical implications of the management strategies applied during the reference period.